Dimensiones de los arcos dentarios deciduos en niños de 5 años en centros educativos en el Cantón Catamayo, Provincia de Loja, período Octubre 2019 - Marzo 2020 - Quito Salcedo, Adriana Elizabeth (2020)
The purpose of this study was to determine and analyze the dimensions of the dental arches. The research is of a descriptive, observational and transversal type in which 50 children were selected: 25 boys and 25 girls of 5 years of age with complete dentition decided in the educational centers of the Catamayo canton by means of criteria of exclusion and inclusion; to which an intra-oral clinical examination was made with the taking of impressions to obtain a registry of models. In the research, dimensions were evaluated by means of the chi-square test to make the comparison according to gender; and these data were statistically analyzed by means of the SPSS program. The arch dimensions were determined: maxillary arch length of 27.5 mm and mandibular arch length of 24.1 mm; arch circumference in the maxilla of 83.7 mm and in the mandible of 76.9 mm; maxillary intercanine width of 29.1 mm and in the mandible of 23.3 mm; intermolar width in the maxilla of 38.6 mm, while in the mandible of 34.5 mm; palatal height of 12.8 mm; the most common arch form is the ovoid with 68.0 %; the presence of primate spaces was more frequent in the maxilla with 74.0 %, while in the mandible only 14.0 % are found. When analyzed and related according to sex, a statistical difference was found (p<0.05) only in the maxillary intermolar width. Keywords: arch dimension, deciduous tooth, dental arch